Analysis and optimization of automotive A-pillar according to fmvss 216 standard - De la Hera Monge, Víctor; Valladares, David; Castejón, Luis (Jornada de Jóvenes Investigadores del I3A, 2021)
Analysis of the rollover behavior of the Geo Metro vehicle in accordance with the US transport standard FMSS216, comparing different types of steel to check how each one behaves when the vehicle is subjected to a rollover load and to deduce which one is the most suitable for the safety and weight reduction of the vehicle.